Amerika: was der Einwanderer wissen sollte (C.V. Zeitung, 1938)
Page from C.V.-Zeitung (Central-Verein-Zeitung), a Jewish newspaper published in Berlin from 1922-1938. features an aritcle titled Amerika/ was der einwanderer wissen sollte (America: what the immigrant should know). on the reverse is the Jewish Literature Section.
Keywords: Jewish newspapers; German newspapers; Newspapers; Emigration and immigration; Third Reich